Uzbek Pilgrimage Tourism Terminology: Lexical and Semantic Analysis - Saidovna , Vakhidova Fatima; Otamurodovna , Fakhriyeva Dilorom (Miasto Przyszłości, 2025)
This article examines the terminology used in Uzbek pilgrimage tourism from a linguistic perspective. It focuses on the lexical and semantic features of the terms, analyzing their meanings, origins, and usage in different contexts. The study aims to identify the distinctive characteristics of pilgrimage-related terms and their role in communication within the tourism sector. The findings contribute to a deeper understanding of the linguistic aspects of pilgrimage tourism and provide insights for the development of standardized terminology in this field. By identifying the distinctive characteristics of pilgrimage-related terminology, the research highlights their role in communication within the tourism sector and their impact on intercultural interactions. The findings contribute to a deeper understanding of the linguistic aspects of pilgrimage tourism and provide insights for the development of standardized terminology in this field, which can be useful for researchers, linguists, and professionals in tourism and translation studies.